Perceived Individualized Care and the Satisfaction Levels of Patients Hospitalized in Internal Medicine Departments: A Cross-Sectional and Correlational Survey - Kilic, Hulya Firat; Su, Serpil; Gok, Nur Demet (Marmara Univ, Inst Health Sciences, 2022)
Objective: Individualized nursing care, which indicates the belief on the uniqueness and worthiness of human beings, improves the quality of healthcare and contributes to patient satisfaction. The aim of this study is to determine the relationship between the perceived individualized care and the level of satisfaction with nursing care for patients hospitalized in internal medicine departments. Methods: This study was carried on 250 patients hospitalized in internal medicine department of a university hospital in Turkey between December 2019 and February 2020. Patient information form, individualized care scale and the Newcastle satisfaction with nursing scale were used for data collection. Mann-Whitney U, Kruskal-Wallis H and Spearman's rho correlation test were used for data analysis. Results: Participants believed that the nursing interventions supported their individuality and had positive perceptions about the individuality in their own care. They were highly satisfied with the nursing interventions. Besides there was a positive correlation between the scores obtained from the individualized care scale and Newcastle satisfaction with nursing scale. Finally, age and education levels of the patients had a positive impact on perceived individualized care and the level of satisfaction with nursing care. Conclusion: The findings suggest that individuality of each patient should be prioritized during the nursing interventions in order to increase patient satisfaction and improve the quality of nursing care.
Keywords: Individualized care; patient satisfaction; nursing care; nursing